Interventions for increasing return to sport rates after an anterior cruciate ligament reconstruction surgery: A systematic review - Drole, K.; Paravlic, A. H. (Frontiers in Psychology, 2022)
Background: An injury followed by surgery poses many challenges to an athlete, one of which is rehabilitation, with the goal of returning to sport. While total restoration of physical abilities is a primary goal for most athletes, psychosocial factors also play an important role in the success of an athlete's return to sport (RTS). The purpose of this review was to examine the effectiveness of exercise and psychosocial interventions on RTS rates, which might be one of the most important outcomes for elite athletes.